Perbandingan dan Hubungan Bobot Hidup dengan Bobot Karkas Ayam Broiler yang Ditambahkan Jagung Kuning pada Pakan Komersial - Ertina Ertina; Kastalani Kastalani; Yemima Yemima; Kristina Kristina (Fakultas Peternakan Universitas Kristen Palangka Raya, 2021)
This study aims to determine the comparison between live weight and carcass weight of broiler chickens added with yellow corn for commercial purposes. To determine the relationship between live weight and carcass weight of broiler chickens added with yellow corn in commercial feed. The research was conducted at the practice and research location of the Faculty of Animal Husbandry, Palangka Raya Christian University. The measurement aspect includes the independent variable (live weight) and the dependent variable (carcass weight). Test the effect of independent variables on the dependent variable with a simple linear regression statistical test with a real test level of 0.05. Data processing used SPSS version 17 computer program and the study used 80 broiler chickens and each treatment used 4 tails. The results of this study showed that the ratio between live weight and carcass weight of broiler chickens added with yellow corn in commercial feed was quite high, ranging from 69.48-71.54%. And the correlation ranged between (r = 0.566-0.975). There is a very strong relationship between live weight and carcass weight of broiler chickens, namely in treatment B (5% yellow corn + 100% BR) and treatment C (10% yellow corn + 100% BR), while a strong relationship is in treatment A (without yellow corn) and treatment D (15% yellow corn + 100% BR). Keywords : Regression, broiler chicken, carcass weight